The role of immersive media in engaging Singapore's history & cultural heritage: Singapore history gallery and digiMuse as a case study (2006-2018) - Cheng, Merlin Shao Meng (Nanyang Technological University, 2023)
This thesis investigates the role of (digital) immersive media (IM); such as virtual reality (VR); augmented reality (AR); mixed reality (MR); immersive environment (IE); among others; in the context of the National Museum of Singapore (NMS) from 2006 to 2018. It acknowledges that digital IM is a small part of the NMS's larger exhibition planning strategy as the NMS’s institution trend. The discussion begins with the intertwining history of the NMS, the National Heritage Board, and immersive media development. The thesis will focus on the 2006 and 2015 iterations of the Singapore History Gallery, which were exhibited differently before and after the revamp from 2014-2015. It will discuss two specific examples in the museum’s 2018 DigiMuse programme and how they suggest that the NMS was serious about working with local and overseas technology companies to enhance the museum experience. The thesis also discusses the NMS adaptability in using IM to engage with their audiences by creating offsite experiences at a time when museum capacity was limited. It looks at how the NMS compare to two other museums in Singapore in creating onsite and offsite IM experiences – ArtScience Museum (ASM) and Asian Civilisations Museum (ACM). Lastly, this thesis looks at how new technology is reshaping the museum-going experience and some best practice frameworks of using IM technology by keeping it short, and simple to use and creating a personal connection with the visitor to meaningfully engage, enrich, and excite them with the exhibition’s content.